An Experimental Test of a Causal Link between Problem-Solving Performance and Reproductive Success in Wild Great Tits - Cauchard, Laure; Angers, Bernard; Boogert, Neeltje J.; Lenarth, Mélissa; Bize, Pierre; Doligez, Blandine (Frontiers in Ecology and Evolution, 2017)
Recent studies have uncovered relationships between measures of various cognitive performances and proxies of fitness such as reproductive success in non-human animals. However, to better understand the evolution of cognition in the wild, we still have to determine the causality of these relationships and the underlying mechanisms. The cognitive ability of an individual may directly influence its ability to raise many and/or high quality young through for example its provisioning ability. Conversely, large and/or high quality broods may lead to high parental motivation to solve problems related to their care. To answer this question, we manipulated reproductive success through brood size and measured subsequent problem-solving performance in wild great tit parents. Our results show that brood size manipulation did not affect the probability to solve the task. Moreover, solver pairs fledged more young than non-solver pairs independently of brood size treatment in one of the two experimental years and they showed higher nestling provisioning rate in both years. Overall, it shows that problem-solving performance was not driven by motivation and suggest that problem-solvers may achieve higher fledging success through higher provisioning rates. Our study constitutes a first key step towards a mechanistic understanding of the consequences of innovation ability for individual fitness in the wild.